Integrated time-series biochemical, transcriptomic, and metabolomic analyses reveal key metabolites and signaling pathways in the liver of the Chinese soft-shelled turtle (Pelodiscus sinensis) against Aeromonas hydrophila infection - Ji, Liqin; Chen, Chen; Zhu, Junxian; Hong, Xiaoyou; Liu, Xiaoli; Wei, Chengqing; Zhu, Xinping; Li, Wei (Frontiers in Immunology, 2024)
Introduction Aeromonas hydrophila, a bacterium widely distributed in the natural environment, causes multiple diseases in various animals. Exploring the mechanism of the host defense against A. hydrophila can help develop efficient strategies against Aeromonas infection. Methods Herein, we investigated the temporal influence of A. hydrophila on the Chinese soft-shelled turtle, an economically important species, at the biochemical, transcriptomic, and metabolomic levels. Plasma parameters were detected with the test kits. Transcriptome and metabolome were respectively applied to screen the differentially expressed genes and metabolites. Results The contents or activities of these plasma parameters were significantly increased at 24 hpi and declined at 96 hpi, indicating that 24 and 96 hpi were two important time points during infection. Totals of 3121 and 274 differentially expressed genes (DEGs) from the transcriptome while 74 and 91 differentially abundant metabolites (DAMs) from the metabolome were detected at 24 and 96 hpi. The top DEGs at 24 hpi included Ccl2, Ccl3, Ccl4, Il1β, Il6, Il7, Il15, Tnf, and Tnfr1 while Zap70, Cd3g, Cd8a, Itk, Pik3r3, Cd247, Malt1, and Cd4 were the most abundant at 96 hpi. The predominant DAMs included O-phospho-L-serine, γ-Aminobutyric acid, orotate, L-tyrosine, and L-tryptophan at 24 hpi, as well as L-glutamic acid, L-arginine, glutathione, glutathione disulfide, and citric acid at 96 hpi. Discussion The combined analysis of DEGs and DAMs revealed that tryptophan metabolism, nicotinate and nicotinamide metabolism, as well as starch and sucrose metabolism, were the most important signaling pathways at the early infective stage while tyrosine metabolism, pyrimidine metabolism, as well as alanine, aspartate and glutamate metabolism were the most crucial pathways at the later stage. In general, our results indicated that the Chinese soft-shelled turtle displays stage-specific physiological responses to resist A. hydrophila infection.